THE INFLUENCE OF MILK PROTEIN CONCENTRATE ON PROPERTIES OF HYDROCOLLOIDS - Elena Karlenovna Tunieva; Viktoriay Viktorovna Nasonova; Kirill Igorevich Spiridonov (Современная наука и инновации)
The article presents the results of studies of the joint use of milk protein and polysaccharide gelators. It has been established that the addition of milk protein concentrate to kappa-carrageenan and xanthan gum solutions improves the functional characteristics of polysaccharide gellants. Addition of salt helps to reduce the strength characteristics of gels. The optimal ratio of the investigated concentrate of whey protein and kappa-carrageenan is 1:1.